Oxidative damage of canine erythrocytes after treatment with non-steroidal anti-inflammatory drugs - Lieser, Julia; Schwedes, Claudia; Walter, Maria; Langenstein, Judith; Moritz, Andreas; Bauer, Natali (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2021)
Objective To investigate oxidative erythrocyte damage in dogs treated with different non-steroidal anti-inflammatory drugs.Material and methods Case-controlled prospective observational study using blood obtained from dogs presenting for lameness examinations or standard surgical procedures to a private referral clinic. Sampling was performed from April 2018 to July 2019. Groups comprised dogs receiving either metamizole (dipyrone) (22 dogs), carprofen (20 dogs) or meloxicam (20 dogs) for a minimum of 10 days. Dogs with gastrointestinal hemorrhage were excluded from the study. A complete hematological, as well as a basic biochemical profile were performed in every dog. Pappenheim stained blood smears were evaluated for eccentrocytes and brilliant cresyl blue stained smears for Heinz bodies. EDTA blood was frozen at –80°C immediately after sampling for measurement of superoxide dismutase and gluthathione peroxidase activity at an external laboratory. Hemoglobin concentration, superoxide dismutase and gluthathione peroxidase activities, reticulocyte count, eccentrocyte and Heinz body numbers were determined prospectively as key parameters for further statistical assessment with Kruskal-Wallis test and Dunn’s multiple comparisons test.Results Dogs receiving metamizole showed a significant increase in eccentrocyte (median 14.5/500 cells vs. 0/500 cells in the other groups, p < 0.0001) and reticulocyte number (median 191.4 × 109/l vs. 31.6–37.9 × 109/l, p < 0.0001) and a significant decrease in hemoglobin concentration (median 8.4 mmol/l vs. 10.1–10.5 mmol/l, p < 0.0003). No significant difference in superoxide dismutase and gluthathione peroxidase activities was observed between dogs receiving metamizole and the other groups. Heinz bodies were not found in any of the dogs.Conclusion Treatment with metamizole for 10 or more days resulted in decreased hemoglobin concentration, eccentrocytosis and reticulocytosis in dogs in this study. This might be a sign of increased oxidative damage caused by this drug.Clinical significance Prolonged metamizole therapy should be evaluated critically in patients already affected by severe illness or underlying anaemia.
Keywords: Dog; eccentrocytes; metamizole; dipyrone; carprofen; meloxicam